Do circular economy business models capture intended environmental value propositions?. (10th January 2018) - Manninen, Kaisa; Koskela, Sirkka; Antikainen, Riina; Bocken, Nancy; Dahlbo, Helena; Aminoff, Anna
Abstract: The circular economy (CE) can be a driver for sustainability and CE can be promoted and supported by the creation of new and innovative business models, which embed CE principles into their value propositions throughout the value chains. This study focuses on the environmental value propositions of the CE business models. The term environmental value proposition refers here to an absolute value being a promise of environmental improvement, which a company provides to the environment by its impacts throughout the whole value chain. The aim of this study is to outline a framework for evaluating the environmental value propositions of CE business models. The framework consists of an environmental value propositions table (EVPT) and a step-by-step approach towards an evaluation process. The framework was tested in three CE business model cases. The outlined framework enables a better understanding of circular economy principles, combining them with the environmental value proposition. With the framework, companies can plan and design new CE business models or they can verify intended environmental benefits and analyse their contribution to sustainability. The biggest challenges, when applying the framework, were related to the estimation of environmental benefits gained from the environmental value propositions at the system level. In the future, intensive scientific work should concentrate on developing environmental assessment methods specifically for companies developing new CE business models.